Epitaxial GaN using Ga(NMe2)3 and NH3 plasma by atomic layer deposition. Issue 25 (2nd June 2020) - Rouf, Polla; O'Brien, Nathan J.; Buttera, Sydney C.; Martinovic, Ivan; Bakhit, Babak; Martinsson, Erik; Palisaitis, Justinas; Hsu, Chih-Wei; Pedersen, Henrik
Abstract : GaN is grown epitaxially on 4H-SiC without buffer layer using ALD with Ga(NMe2 )3 and NH3 plasma. Abstract : Low temperature deposition of high-quality epitaxial GaN is crucial for its integration in electronic applications. Chemical vapor deposition at approximately 800 °C using SiC with an AlN buffer layer or nitridized sapphire as substrate is used to facilitate the GaN growth. Here, we present a low temperature atomic layer deposition (ALD) process using tris(dimethylamido)gallium(iii ) with NH3 plasma. The ALD process shows self-limiting behaviour between 130–250 °C with a growth rate of 1.4 Å per cycle. The GaN films produced were crystalline on Si (100) at all deposition temperatures with a near stochiometric Ga/N ratio with low carbon and oxygen impurities. When GaN was deposited on 4H-SiC, the films grew epitaxially without the need for an AlN buffer layer, which has never been reported before. The bandgap of the GaN films was measured to be ∼3.42 eV and the Fermi level showed that the GaN was unintentionally n-type doped. This study shows the potential of ALD for GaN-based electronic devices.